2013
DOI: 10.1002/jemt.22307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interaction between sodium hypochlorite and several formulations containing chlorhexidine and its effect on the radicular dentin—SEM and push‐out bond strength analysis

Abstract: The aim of the current study was to evaluate the presence of debris and smear layer after endodontic irrigation with different formulations of 2% chlorhexidine gluconate (CHX) and its effects on the push-out bond strength of an epoxy-based sealer on the radicular dentin. One hundred extracted human canines were prepared to F5 instrument and irrigated with 2.5% sodium hypochlorite and 17% ethylenediaminetetraacetic acid. Fifty teeth were divided into five groups (n = 10), according to the final irrigation proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…, Graziele Magro et al . ). However, the chemical composition of this precipitate is questionable because through nuclear magnetic resonance spectroscopy analysis, it has been observed that a mixture of NaOCl and chlorhexidine acetate does not produce PCA (Thomas & Sem ).…”
Section: Introductionmentioning
confidence: 97%
“…, Graziele Magro et al . ). However, the chemical composition of this precipitate is questionable because through nuclear magnetic resonance spectroscopy analysis, it has been observed that a mixture of NaOCl and chlorhexidine acetate does not produce PCA (Thomas & Sem ).…”
Section: Introductionmentioning
confidence: 97%
“…The length was standardized at 15 mm using an Isomet cutting machine (Isomet 1000, Buehler Ltd, Lake Bluff, IL, USA) with a diamond disc at 250 revolutions per minute (rpm), under irrigation, reducing the height of the tooth crown and gaining access to the canal 18 . The patency was performed by inserting a # 15 K file (Dentsply, Maillefer, Ballaigues, Switzerland) until the tip of the instrument was seen juxtaposed to the apical foramen 19,20 . Soon after, 1mm was subtracted from this measurement, obtaining a working length of 14mm.…”
Section: Preparation Of Teethmentioning
confidence: 99%
“…The root apex of each specimen was closed with pink wax # 7, avoiding the extrusion of irrigants 20,21 . The specimens were inserted into a sterile metallic device and adjusted until they were firm.…”
Section: Preparation Of Teethmentioning
confidence: 99%
“…All specimens were kept moist by keeping them in gauze moistened with sterile saline solution, and were incubated for 7 days at 37 o C with 100% humidity (12) .…”
Section: Specimens' Obturationmentioning
confidence: 99%